Imaging study of aseptic loosening of the acetabular cup after cementless total hip arthroplasty: a retrospective study - Aoyang He; Yao Zhang; Chunmiao Lu; Lei Cao; Jicun Liu; Zhiwei Zhong (BMC Musculoskeletal Disorders)
Abstract Purpose The purpose of this study was to provide more accurate imaging diagnostic parameters for acetabular cup loosening through radiological characteristic of acetabular cup aseptic loosening after cementless total hip arthroplasty, especially for patients lacking postoperative baseline or serial follow-up radiographs. Methods The radiographic data of patients who underwent primary unilateral cementless total hip arthroplasty in our hospital from January 2017 to July 2024 were retrospectively studied. Forty-one patients with aseptic loosening of the acetabular cup, confirmed by surgery or consensus between clinicians and radiologists, were included in the loosening group. Sixty-one patients who underwent primary total hip arthroplasty and were evaluated more than one year postoperatively were included as the control group. The absence of postoperative complications was confirmed through discussions between clinicians and radiologists. Radiographic examination of the contralateral hip joint in all included patients showed no significant abnormalities. The following imaging parameters were measured on anteroposterior bilateral hip radiography: acetabular cup inclination (AA), acetabular difference in vertical distance 1 (DVD1), acetabular difference in vertical distance 2 (DVD2), acetabular difference in horizontal distance (DHD), wide radiolucent zones around the acetabular cup (TA), number of wide radiolucent zones around the acetabular cup (NTA) and difference in head-cup edge distance (DHCD). Results The numerical value of TA, DVD1, DHCD, AA and NTA in the loosening group was significantly higher than in the control group, and the differences were all statistically significant (P < 0.05). The critical values of DVD1, DHCD, AA and NTA were 1.49 cm, 0.16 cm, 53.2 ° and 1, respectively. The combined imaging diagnostic criteria for acetabular cup loosening are defined as the simultaneous fulfillment of the following two conditions: (1) NTA ≥ 1; (2) AA ≥ 53.2° or DHCD ≥ 0.16 cm. The results of the validation analysis were statistically significant. Conclusions The combined imaging diagnostic criteria for aseptic loosening of the acetabular cup after total hip arthroplasty, established in this study, demonstrate superior diagnostic efficacy compared to single imaging parameters. This approach does not rely on postoperative baseline radiographs or serial follow-up radiographs and can accurately determine the specific location of prosthetic loosening.